Bio-pulsating architecture for object-based processing in next generation vision systems - Constandinou,TG; Lande,TS; Toumazou,C (Electronics Letters, 2003)
A novel and robust distributed architecture for real-time object-based processing is presented for tasks such as object size, centre and count determination. This approach uses the input image to enclose a feedback loop and realise a data-driven pulsating action, ideally suited for implementation in standard CMOS technologies.